Numerical simulation of fractal interface effect of mining-caused activation of fault - Yu Guangming; Zhao Jianfeng; Xie Heping (Discrete Dynamics in Nature and Society)
Mining-caused activation of fault is an important research subject in mining science. In the past, the influences of geometrical morphology of fault surface on the activation have not been revealed. In view of the fractal character of fault surface, the self-affine fractal curves and geological-mining models with these kinds of fractal fault surface are constructed in order to numerically simulate the mining-caused activation phenomenon of fractal fault surface, and the law of influence of fractal fault surface on mining subsidence is studied and summarized. Our study shows that the mining-cased activation of fault has remarkable fractal interface effect; the mechanical behavior of mining-caused shearing sliding of fault is correlated with its fractal dimension, and after mining-caused activation fault surface with different fractal dimensions will result in different stress fields and different displacement fields in the nearby rock mass.